PENGARUH PENERAPAN AKUNTANSI BERBASIS AKRUAL DALAM MEMINIMALISIR FRAUD TERHADAP KINERJA UMKM DENGAN VARIABEL MODERASI KUALITAS SUMBER DAYA MANUSIA (SDM) - Hamdani Hamdani; Firdayanti Firdayanti; Nurhikmah Nurhikmah (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyse the effect of accrual-based accounting on minimising fraud in SME performance, with human resource quality as a moderating variable. Accrual-based accounting is expected to improve the transparency and accuracy of financial reports, which in turn can reduce the potential for fraud in SME financial management. This study uses a quantitative approach with a survey method on MSMEs in Palopo City. The data obtained was analysed using moderation regression to test the relationship between variables. The results show that the application of accrual-based accounting has a positive effect in minimising fraud and improving MSME performance. In addition, HR quality is proven to be a moderating variable that strengthens this relationship. These findings have practical implications for MSMEs to prioritise the implementation of accrual-based accounting and the development of human resource quality in an effort to improve performance and reduce fraud